Yayasan UMP will launch special registration number under strategic collaboration with Aquatwo - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 22 November 2021 - Universiti Malaysia Pahang (UMP) will launch a special series of number plates UC1 to UC9999 which are only offered to the public through bidding after the completion of the gazetting process towards UMP’s 20th anniversary celebration next year.